Kasambahay, kasampamilya investigating the familial relationship of care workers and their employer - Carlos, Gabrielle Anne S.; Roman, Rinoa Clarisse V.; Ugaddan, Miriam I. (Quezon City University of the Philippines Diliman, 2025)
This study invenstigates the relationship between live-in kasambahay (LIK) and their employees (amo), focusing on the care provided and interaction dynmaics. It amis to understand the experences of both LIKs navigating their roles within the families and the amos receiving care work. The research seeks to examin the nature of the familial relationships that evolve between LIKs and their amos. Five pairs of LIK-Amo from Makati City were chosen carefully through purposive sampling for semi-structured interviews. These interviews are patterened after the Sikolohiyang Pilipino practice of pakikipagkwentuhan, which facilitiates in-depth dialogues about experiences and feelings. The data was collected and analyzed through thematic analysis. Results showed that the care work experiences of the LIKs encompasses both their formal work experiences and the emotional bods developed with their amo. On the amo's perspectives on care work. their experiences revolved around the reasons for employing LIK and the deepy felt personal advantages. Overall, the familial relationshiop formed between the LIK and amo is generally a consequence of the extended employment period and the inherently intimate experiences of care work. The research findings can foster a heightened awareness and understanding of the intricate dynamics of LIKs and the broader field of care work in the Philippines, especially by highlighting this essntial yet often marginalized sector in labor and general discourses.
In partial fulfillment for the Degree of Bachelor of Science in Family Life and Child Development
Thesis
Keywords: Household employees -- Philippines; Industrial relations; Caregivers -- Services for -- Philippines; Labor -- Social aspects; Sikolohiyang Pilipino; Care work; Domestic work; Live-in kasambahay (LIK).; Familial relationship